Dynamic Subcellular Localization, Accumulation, and Interactions of Proteins From Tomato Yellow Leaf Curl China Virus and Its Associated Betasatellite - Li, Hao; Li, Fangfang; Zhang, Mingzhen; Gong, Pan; Zhou, Xueping (Frontiers in Plant Science, 2020)
Geminiviruses contain the largest number of species of plant viruses, and cause devastating crop diseases worldwide. The development of resistance to these viruses will require a clear understanding of viral protein function and interactions. Tomato yellow leaf curl China virus (TYLCCNV) is a typical monopartite geminivirus, which is associated with a tomato yellow leaf curl China betasatellite (TYLCCNB) in the field; the complex infection of TYLCCNV/TYLCCNB leads to serious economic losses in solanaceous plants. The functions of each protein encoded by the TYLCCNV/TYLCCNB complex have not yet been examined in a targeted manner. Here, we show the dynamic subcellular localization and accumulation of 6 viral proteins encoded by TYLCCNV and the βC1 protein encoded by TYLCCNB in plants over time, and analyzed the effect of TYLCCNV or TYLCCNV/TYLCCNB infection on these parameters. The interaction among the 7 viral proteins was also tested in this study: C2 acts as a central player in the viral protein interaction network, since it interacts with C3, C4, V2 and βC1. Self-interactions were also found for C1, C2 and V2. Together, the data presented here provide a template for investigating the function of viral proteins with or without viral infection over time, and points at C2 as a pivotal protein potentially playing a central role in the coordination of the viral life cycle.